Pengetahuan dan Sikap Ibu terhadap Perawatan Tali Pusat pada Bayi Baru Lahir - Desti Widya Astuti (Citra Delima Scientific journal of Citra Internasional Institute, 2020)
The treatment of umbilical cord is a medical and tying of it wich separates mother and baby physically. Then, the umbilical cord is taken care in clean way and avoided from infection. The purpose of the researh was to know the relation between knowledge and mother’s attitude with treatment of umbilical cord in district hospital of prabumulih in 2019. The methode of research was analytic by using cross sectional approach. The population of this research was all of childbirth mothers taken care in midwifery room of district hospital of prabumulih. The sample was accidental sampling technique as many 75 respondents. The instrument of the research was questionare. The conclusion : there was significant relation between knowledge and treatment of umbilical cord with score p-value 0,000 < α 0,05 and there was significant relation between mother’s attitude and treatment of umbilical cord with score p-value 0,000 < α 0,005.